Estrategias de atención de enfermería aplicadas para la prevención del virus de papiloma humano en adolescente de la Comunidad de Barrio Lindo. - Franco Pibaque, Michel Estefanía (2020)
Sexually transmitted diseases are the most common in the country, in fact almost all sexually active people are infected with them, where human papillomavirus infection is listed, Most people with the virus do not have symptomatology so they do not suspect being infected, often due to lack of knowledge; However, some types of HPV can cause genital warts or certain types of cancer. The present study is of a descriptive and explanatory type since it describes the problem posed and explains the causes that originated the analyzed situation, with a quantitative approach in which there is no cause-effect relationship of the studied phenomena allowing to identify the behavior of the adolescents of the Barrio Lindo community in the city of Babahoyo and the nursing professionals who work at the Enrique Ponce Luque Health Center. The sample that participated in the research is 56 adolescents and 8 nursing professionals, using questionnaires formulated with 10 open and closed questions to collect data, to subsequently tabulate analyze, conclude establish recommendations culminating with a Proposal.